2010
DOI: 10.1088/0004-637x/723/2/1829
|View full text |Cite
|
Sign up to set email alerts
|

ERRATUM: “PHYSICAL PROPERTIES OF THE 0.94 DAY PERIOD TRANSITING PLANETARY SYSTEM WASP-18” (2009, ApJ, 707, 167)

Abstract: The published version of this article presented high-precision observations of the transiting extrasolar planetary system WASP-18, which is of particular interest because accurate transit timings over a number of years may provide empirical constraints on the tidal quality factor of the host stars of gas giant planets. We have since discovered that the times recorded in the FITS headers of our observations were offset from the true values. This information was used to generate the timestamps in the photometric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
74
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(84 citation statements)
references
References 1 publication
9
74
1
Order By: Relevance
“…WASP: The Wide-Angle Search for Planets (WASP) Project (Pollacco et al 2006) announced the discovery and initial orbital solution of WASP-18b as observed in transit by the WASP-South Survey and in radial velocity with the CORALIE spectrograph (Hellier et al 2009), and confirmed with the Danish 1.5m telescope at ESO (Southworth et al 2009). The Southworth et al (2009) Warm Spitzer: Maxted et al (2013) observed two full phases of WASP-18b's orbit with warm Spitzer, one with the 3.6 µm channel on January 23, 2010, and the other with the 4.5 µm channel on August 23, 2010.…”
Section: Results: Transit Timing Evolution Over Nine Yearsmentioning
confidence: 99%
See 1 more Smart Citation
“…WASP: The Wide-Angle Search for Planets (WASP) Project (Pollacco et al 2006) announced the discovery and initial orbital solution of WASP-18b as observed in transit by the WASP-South Survey and in radial velocity with the CORALIE spectrograph (Hellier et al 2009), and confirmed with the Danish 1.5m telescope at ESO (Southworth et al 2009). The Southworth et al (2009) Warm Spitzer: Maxted et al (2013) observed two full phases of WASP-18b's orbit with warm Spitzer, one with the 3.6 µm channel on January 23, 2010, and the other with the 4.5 µm channel on August 23, 2010.…”
Section: Results: Transit Timing Evolution Over Nine Yearsmentioning
confidence: 99%
“…ephemeris was later found to be erroneous(Southworth et al 2010); we use only the Hellier et al (2009) ephemeris. Left: Two new transits of WASP-18 by its planet observed by TRAPPIST in 2015.…”
mentioning
confidence: 99%
“…The 2009 season with the Danish Telescope suffered from a timing problem(Southworth et al 2009c(Southworth et al , 2010. We have investigated this further and found that it did not affect any observations of WASP-4 presented here.…”
mentioning
confidence: 75%
“…Some TEPs have a non‐circular orbit which changes the duration of the transit but has a negligible effect on the light‐curve shape (Kipping 2008). I account for this by adding published constraints on orbital eccentricity ( e ) and periastron longitude (ω), with the parameter combinations e cos ω and e sin ω when possible, using the approach outlined in Paper III and Southworth et al (2009c).…”
Section: Analysis Of the Light Curvesmentioning
confidence: 99%